PENGARUH KEGIATAN FINGER PAINTNG TERHADAP PENINGKATAN KEMAMPUAN MOTORIK HALUS ANAK USIA4-5 TAHUN DI TK AISYIYAH BUSTANUL ATHFAL BAHAGIA KOTA MAKASSAR - Reskianti; Abdul Saman; Rika Kurnia; Herlina; Kartini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to 1) determine the fine motor skills of group A children before and after being given treatment in the form of finger painting activities at the Aisyiyah Bustanul Athfal Bahagia Kindergarten, Makassar City; 2) determine the application of finger painting activities to the development of fine motor skills in children at the Aisyiyah Bustanul Athfal Bahagia Kindergarten, Makassar City; 3) determine the effect of finger painting on the development of fine motor skills in children at the Aisyiyah Bustanul Athfal Bahagia Kindergarten, Makassar City. The research design uses Quasi Experimental Design. The data collection techniques used in this research are observation, tests and documentation. The subjects in this study were 10 people in the control group and 10 people in the experimental group. The results of the research show that there is a significant influence in providing finger painting activities on improving the fine motor skills of children aged 4-5 years at Aisyiyah Bustanul Athfal Bahagia Kindergarten, Makassar City, with the results showing that the value obtained from coloring activities for the control class is Asymp 0.102 . The results of the calculation of finger painting activities for the experimental class obtained an Asymp Sig (2-tailed) value of 0.005<0.05.